A Life among Men, Women and Molecules. Memoirs of an Indian Scientist. By MaMannaMana Vijayan. Indian National Science Academy, 2020. Ebook, pp. xi+305. ISBN 978‐81‐939482‐6‐2. Price USD 35.00 INR 1500. Issue 11 (2nd November 2020) - Baker, Edward N.
Abstract : A review of the autobiography of one of India's the most important scientists, MaMannaMana Vijayan. Abstract : A review of the autobiography of one of India's the most important scientists, MaMannaMana Vijayan.